Synchrotron XRF and XANES investigation of uranium speciation and element distribution in fluid inclusions from unconformity‐related uranium deposits. Issue 2 (23rd December 2012) - Richard, A.; Cauzid, J.; Cathelineau, M.; Boiron, M.‐C.; Mercadier, J.; Cuney, M.
Abstract Fluid inclusions from two quartz samples of the McArthur River and Rabbit Lake unconformity‐related uranium deposits (Athabasca Basin, Canada) were analysed by synchrotron X‐ray fluorescence (SXRF) and X‐ray absorption near‐edge spectroscopy (XANES) to shed light on (i) the detailed chemistry of the fluids having transported the uranium and (ii) the speciation of uranium in these fluids. The analysed samples contain variable proportions of NaCl‐rich or CaCl2‐rich (25–35 wt% salts) fluid inclusions that homogenise into the liquid phase between 120 and 200°C. For unknown reason, all of the CaCl2‐rich fluid inclusions decrepitate under X‐ray beam after a few seconds, precluding any SXRF or XANES measurement. SXRF on 12 homogenised NaCl‐rich fluid inclusions from the Rabbit Lake sample shows that the fluid inclusions contain appreciable amounts of Br, Fe, Sr, transition metals (Mn, Ni, Cu, Zn), Pb, U and rare earth elements (REE) (La, Ce), with concentrations being relatively homogeneous among fluid inclusions. Within the complex McArthur River sample (numerous fluid inclusions + randomly distributed solids), statistical analyses of hyperspectral SXRF images were performed using the non‐negative matrix approximation (NNMA) method. This strategy allows distinguishing the three domains contributing to the overall signal: (i) the quartz matrix, which notably contains significant amounts of Cr, Cu and Pb; (ii) the fluid inclusions characterised by high amounts of Br, Fe, Sr and transition metals; and (iii) La‐Ce ± Fe solids. Part of the U and REE are spatially associated with distinct optically invisible solids within the quartz matrix. XANES on four McArthur River sample fluid inclusions at room temperature and at 150°C (fluid inclusion trapping temperature) as well as in solid and liquid U(IV) and U(VI) standards, respectively, shows that the uranium has remained in the form of U(VI) from trapping to present in the fluid inclusion.